2019
DOI: 10.18203/2394-6040.ijcmph20192831
|View full text |Cite
|
Sign up to set email alerts
|

A prevalence study of ocular manifestations in HIV positive patients on highly active anti-retroviral therapy

Abstract: Background: Among 40 million cases worldwide, 50-75% of patients have at least one ocular manifestation in their lifetime. Many of ocular infections are treatable with therapeutic agents. Ocular manifestations invariably reflect systemic disease and can be the initial manifestations of HIV in many cases. Understanding of ocular sequel of HIV infection can lead to the early diagnosis and effective treatment. This study emphasizes on the need of developing a specific ophthalmic examination for the management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Adnexal involvement, anterior segment involvement, posterior segment involvement, neuro-ophthalmic abnormalities, and orbital involvement all occurred in 20%, 28%, 33%, and 4% of these cases, respectively. In total, 51% of patients had CD4+ T cell counts under 200 cells/L, and 76% were in the WHO clinical stages 2 and 3 [ 24 ]. We observed that infectious eye diseases were more frequent in cases with CD4 levels of <200/mL and 201–499/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Adnexal involvement, anterior segment involvement, posterior segment involvement, neuro-ophthalmic abnormalities, and orbital involvement all occurred in 20%, 28%, 33%, and 4% of these cases, respectively. In total, 51% of patients had CD4+ T cell counts under 200 cells/L, and 76% were in the WHO clinical stages 2 and 3 [ 24 ]. We observed that infectious eye diseases were more frequent in cases with CD4 levels of <200/mL and 201–499/mL.…”
Section: Discussionmentioning
confidence: 99%